Impact of TRMT6 on prognosis and immune microenvironment in ovarian cancer - Zhao, Jing; Wang, Xiaona; Wang, Yazhuo; Li, Na (Frontiers in Oncology, 2025)
PurposeThis study investigates the impact of the m1A regulator TRMT6 on prognosis and the tumor microenvironment in ovarian cancer.MethodsAn analysis of the TCGA database was conducted, supplemented by validation from clinical specimens (13 paired samples), to systematically evaluate the expression characteristics of 10 m1A regulators. The prognostic value was assessed using the Kaplan-Meier Plotter database and Cox regression analysis. Additionally, immunohistochemistry and the Log-rank test were employed to validate the impact of TRMT6 on the prognosis and clinicopathological characteristics of ovarian cancer patients. The ssGSEA algorithm and CIBERSORT were utilized to analyze the influence of TRMT6 on the tumor immune microenvironment. We performed single-gene differential analysis of TRMT6 in the TCGA ovarian cancer database using the DESeq2 package and constructed a ceRNA network.ResultsThree m1A regulators (TRMT10C, TRMT6, YTHDF1) were significantly overexpressed in cancer tissues (p < 0.01). Specifically, among these, TRMT6 and YTHDF1 were significantly associated with lower progression-free survival and overall survival (OS) (p < 0.01). Notably, TRMT6 emerged as an independent prognostic factor for predicting poor overall survival (HR = 2.74; 95% CI, 1.13 - 6.65; P = 0.026). TRMT6 expression had a significant correlation with the pathological stage. Furthermore, TRMT6 expression exhibited a significant negative correlation with eleven tumor-infiltrating immune cell types, including cytotoxic cells (p < 0.01). We also found that in ovarian cancer tissues with high expression of TRMT6, the enrichment scores of T cells gamma delta (p < 0.01) and Mast cells activated (p < 0.05) were significantly lower than those in tissues with low expression. HPSE2 has the most interaction nodes among mRNAs, hsa-miR-17-5p among miRNAs, and Lnc SNHG14 among lncRNAs in the ceRNA network.ConclusionThe findings suggest that the m1A regulator TRMT6 may drive ovarian cancer progression by promoting immune escape.